Comparative analysis of the Gran Dolina-TD6 (Spain) and Tighennif (Algeria) hominin mandibles - José-Maria Bermúdez de Castro; Maria Martinón-Torres; Aida Gómez-Robles; Leyre Prado; Susana Sarmiento (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
We present a comparative study of the Tighennif (Algeria) and Gran Dolina-TD6 (Spain) hominin mandibles, which represent two geographically near and contemporaneous populations separated by the Mediterranean sea, in order to test the hypothesis that these populations belong to the same evolutionary lineage, as it has been suggested by some authors. The Tighennif mandibles show a clear primitive structural pattern, derived in some features with regard to the oldest Homo specimens from H. habilis, as well as from the Javanese H. erectus. In addition, the Tighennif specimens share all these derived features with H. ergaster and, some of them, with H. antecessor. However, the Gran Dolina-TD6 specimens are remarkably smaller than those of Tighennif, and lack the robustness which characterizes the African Pleistocene mandibles. The main difference between both groups in terms of mandibular dimensions can be related to the higher corpus height characteristic of Tighennif specimens. The dental evidence reveals that North African Middle Pleistocene populations are morphologically closer to African Early Pleistocene populations than to TD6 fossils. We conclude that the Spanish and Algerian hominins belong to different hominin lineages. The Tighennif hominins, together with other contemporaneous (Thomas Quarry and Oulad Hamida 1), and perhaps later North African specimens (Sidi Abderrahaman, Salé, and Rabat [Kebitat]) should be considered as a subspecies of the H. ergaster species, i.e. H. ergaster mauritanicus, and may be the result of an evolution in isolation in this African area. In agreement with the mandibular and dental evidences, the Gran Dolina-TD6 hominins could belong to an exclusive Eurasian lineage.